The impact of hip rotator strength training on agility in male high school soccer players - Nelson, J. O.; DeBeliso, M. (The Sport Journal, 2014)
The strength of the muscles surrounding a joint contributes to the stability of the joint. The stability of a joint provides the foundation for large muscle groups to perform high speed forceful actions. The purpose of this study was to examine if strengthening of the hip rotator muscles could improve measures of agility.